Effectiveness Of The Incredible Years Parenting Program For Children With Behavioral Problems: An Experience In A Developing Country During A Pandemic - Ruziana Masiran; Normala Ibrahim; Hamidin Awang; Lim Poh Ying; Chan Tze Lin; Sankari Ganesh Narayanasamy (Elsevier, 2024)
Children and Youth Services Review Volume 142, November 2022, 106629